Analisis Kemampuan Pemahaman Mahasiswa Terkait Metode Penyelesaian Soal Persamaan dan Pertidaksamaan - Maisyaroh Maisyaroh; Dinda Indriani Nasution; Afrizal Manurung (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to describe students' difficulties in solving equations and inequalities. This type of research is descriptive using a qualitative approach. Based on the discussion and research results, it can be concluded that the errors that students often make in this material are errors at the reading and transformation stages. In addition, students also often make mistakes at the process skill stage, namely errors in understanding the problem, understanding the concept, determining the correct formula, and performing the calculation process. The factors that cause students to make mistakes are that students are less precise in determining known and questionable information, less precise in compiling problem solving steps, less precise in using formulas, less precise in writing the steps of completion, less precise in performing correct calculations, not determining the conclusion of what is asked, and not re-examining the results of the answers that have been done.